PREVENTING ROAD ACCIDENTS USING CLOUD COMPUTING - Sachin Raj Saxena, Dr. Devendra Singh, Dr. Bhumika Gupta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As innovation and traffic developed, road accidents and road hazards have increased, causing more deaths due to the lack of timely support bureaus. This document aims to respond to timely malicious warning, car burglary monitoring and vehicle contamination alarms. The document that is being submitted registers the limits of the car over time, using a wonderful gadget inserted into the car, and transfers these characteristics to the cloud, car owners or externals. Based on the data, adjustment calculations are performed to give warnings and action. In the event that a malaise occurs after the vehicle and disturbing the car remotely and last, but not least, by watching sensor esteems to convey air contaminating alerts produced by the automobiles, the structure will work with the customers in various ways as a guarantee of fire assistance. The framework is developed using the . Cloud advantages and associated administrations are network systems, MS Access and Microsoft Azzure. The segments of equipment include the vehicle's "shrewd gadget" and a mobile phone for customer cooperation. The so-called "keen gadget" inside the vehicle does not interfere with normal operation or cause overheads.